2006
DOI: 10.1128/jvi.01648-06
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Microglia by Borna Disease Virus Infection: In Vitro Study

Abstract: Neonatal Borna disease virus (BDV) infection of the rat brain is associated with microglial activation and damage to the certain neuronal populations. Since persistent BDV infection of neurons in vitro is noncytolytic and noncytopathic, activated microglia have been suggested to be responsible for neuronal cell death in vivo. However, the mechanisms of activation of microglia in neonatally BDV-infected rat brain have not been investigated. To address these issues, activation of primary rat microglial cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…The selective loss of neurons in experimentally infected newborn rats has been puzzling, since BDV has been repeatedly shown to be noncytolytic in differentiated neurons in cultures (16,31). Our findings support the hypothesis that BDV-induced neurodegeneration is due to BDV interference with neurogenesis.…”
Section: Map2supporting
confidence: 80%
See 2 more Smart Citations
“…The selective loss of neurons in experimentally infected newborn rats has been puzzling, since BDV has been repeatedly shown to be noncytolytic in differentiated neurons in cultures (16,31). Our findings support the hypothesis that BDV-induced neurodegeneration is due to BDV interference with neurogenesis.…”
Section: Map2supporting
confidence: 80%
“…Our results led us to conclude that the presence of the virus during neuronal differentiation induces neuronal death by interfering with signaling pathways which are important for the proper maturation of neurons. Importantly, the effect of BDV on neurons is restricted to developmental stages, since it has been repeatedly shown in previous works that fully differentiated neurons in cultures were not affected by BDV infection (16,31). The BDV impairment of neurogenesis was already suggested in a study by Friedl et al (12), who used an elegant ex vivo model of organotypic hippocampal slice cultures from newborn rat pups.…”
Section: Map2mentioning
confidence: 87%
See 1 more Smart Citation
“…In either mechanism, the brains with downregulated S100B expression might succumb to the stressful environment and cause the apoptosis of neural cells. Previous studies have demonstrated that in BDV-infected neonatal rat brains, reactivation of glial cells may be associated with specific neuronal cell apoptosis rather than viral tropism and virusspecific immune responses (29,50). These studies support our hypothesis that sustained activation of astrocytes in the persistently infected brains may exhaust the glial functions concerned with cellular survival.…”
Section: Discussionsupporting
confidence: 80%
“…The CNS response to ischaemia, degenerative diseases and viral infection is largely manifested by neuronal loss and inflammatory responses (Gao et al, 2002;Liao et al, 2002;Chen et al, 2004;Raung et al, 2005;German et al, 2006;Ovanesov et al, 2006;Ghoshal et al, 2007;van Marle et al, 2007;Saxena et al, 2008;Swarup et al, 2008). Generally, the onset and/or interactive crosstalk of neuronal injury and neuroinflammation play a critical role in the pathogenesis of neurological disorders.…”
Section: Introductionmentioning
confidence: 99%